Digital Flipped Learning by Using Telegram in Teaching Listening and Speaking Skills of University Students l al-Ta’lim al-Maqlub li Maharah al-Istima’ wa al-Kalam bi Istikhdam Telegram Lada Thulab al-Jamiah - Maslamah, Maslamah; Kholis, Muhammad Nur (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
To reduce the rate of development of the virus Covid-19, educational institutions must carry out learning using distance learning models by utilizing technology. This research aims to analyze the process of digital flipped learning of using Telegram in teaching listening dan speaking skills. The methods used in this study are qualitatively descriptive. The data on students’ responses to the teaching process was employed from the survey. The researchers analyzed the process of using Telegram in teaching listening and speaking skills to the 39 Arabic Language and Literature students at IAIN Surakarta. In addition, the effectiveness of using Telegram was measured by the students’ responses. There were two stages of using Telegram: the stage before and while the online class. The stages before online classes include listening and watching video material (knowledge), summarizing, and determining important points (comprehension). The current stages of online classes include students' presentation (application), discussion and Q&A (analysis), giving input (evaluation), and compiling knowledge-thinking critical-problem solving (creation). The results of this study, the average students respond positively to using Telegram in teaching listening and speaking skills. Then digital flipped learning of using Telegram can be used again in teaching these skills.